Increasing heterogeneity in the organization of synaptic inputs of mature olfactory bulb neurons generated in newborn rats - Kelsch, Wolfgang; Sim, Shuyin; Lois, Carlos (The journal of comparative neurology, 2012)
New neurons are added into the mammalian olfactory bulb throughout life, but it remains unknown whether the properties of new neurons generated in newborn animals differ from those added during adulthood. We compared the densities of glutamatergic synapses of granule cells (GCs) generated in newborn and adult rats over extended periods of time. We observed that, whereas adult-born GCs maintained stable cell-to-cell variability of synaptic densities soon after they integrated into the circuit, cell-to-cell variability of synaptic densities of neonatal-born GCs increased months after their integration. We also investigated whether the synaptic reorganization induced by sensory deprivation occurred differently in mature neonatal- and adult-born GCs. Sensory deprivation after new GCs had differentiated induced more pronounced changes in the synaptic densities of neonatal-born GCs than in adult-born GCs. These observations suggest that the synapses of mature neonatal-born GCs retain a higher degree of malleability in response to changes in neuronal activity than adult-born GCs. J. Comp. Neurol. 520:1327-1338, 2012. © 2011 Wiley Periodicals, Inc.